Uptake of, barriers and enablers to the utilization of postnatal care services in Thyolo, Malawi - Alinane Linda Nyondo-Mipando; Marumbo Chirwa; Andrew Kumitawa; Sangwani Salimu; Jacqueline Chinkonde; Tiyese Jean Chimuna; Martin Dohlsten; Bongani Chikwapulo; Mesfin Senbete; Fatima Gohar; Tedbabe D. Hailegebriel; Debra Jackson (BMC, 2023)
Abstract Background Postnatal care (PNC) ensures early assessments for danger signs during the postpartum period and is to be provided within 24 h of birth, 48-72 h, 7-14 days, and six weeks after birth. This study assessed the uptake of and the barriers and facilitators to receiving PNC care among mothers and babies. Methods A concurrent mixed-method study employing a retrospective register review and a qualitative descriptive study was conducted in Thyolo from July to December 2020. Postnatal registers of 2019 were reviewed to estimate the proportion of mothers and newborns that received PNC respectively. Focus Group Discussions (FGDs) among postnatal mothers, men, health care workers, and elderly women and in-depth interviews with midwives, and key health care workers were conducted to explore the barriers and enablers to PNC. Observations of the services that mothers and babies received within 24 h of birth, at 48-72 h, 7-14 days, and six weeks after birth were conducted. Descriptive statistics were tabulated for the quantitative data using Stata while the qualitative data were managed using NVivo and analysed following a thematic approach. Results The uptake of PNC services was at 90.5%, 30.2%, and 6.1% among women and 96.5%, 78.8%, and 13.7% among babies within 48 h of birth, 3 to 7 and 8 to 42 days respectively. The barriers to PNC services included the absence of a baby or mother, limited understanding of PNC services, lack of male involvement, and economic challenges. Cultural and religious beliefs, advice from community members, community activities, distance, lack of resources, and poor attitude of health care workers also impeded the utilisation of PNC services. The enablers included the mother's level of education, awareness of the services, economic resources, community-based health support, adequacy and attitude of health workers, seeking treatment for other conditions, and other clinic activities. Conclusion Optimisation of uptake and utilization of PNC services for mothers and neonates will require the involvement of all stakeholders. The success of PNC services lies in the communities, health services, and mothers understanding the relevance, time points, and services that need to be delivered to create demand for the services. There is a need to assess the contextual factors for a better response in improving the uptake of PNC services and in turn inform the development of strategies for optimizing the uptake of PNC services.